Analysis on alteration of road traffic casualties in western China from multi-department data in recent decade - Qiu, Jinlong; Liu, Guodong; Yang, Ao; Li, Kui; Zhao, Hui; Qin, Mingxin (Frontiers in Public Health, 2022)
Background: Road traffic safety has considerably improved in China. However, the changes may differ in the economically backward and altitude higher western region. This study aims to investigate changes in the occurrence and severity of traffic casualties in western China and illuminate several key causal factors. Materials and Methods: Traffic accident data from the Annual Traffic Accident Statistics Report combined with population and vehicle data from the China Statistics Bureau between 2009 and 2019, were retrospectively analyzed. Traffic accident numbers, fatalities, human damage (HD), case fatality rates (CFR), mortality per 100,000 population (MRP), and mortality per 10,000 vehicles (MRV) were compared between the western and eastern regions. The HD, CFR, MRV, and MRP between the four groups based on the altitude of cities, below 500 meters, 500 to 1500 meters, 1500 to 3000 meters, and over 3000 meters, were compared using one-way analysis of variance. 178 cases of extremely serious traffic accidents were further analyzed in terms of accident characteristics, and accident reason. The differences between the eastern and western regions were compared using the chi-square test. Results: The number of traffic accidents and fatalities decreased in low-altitude areas in western China. However, there was a significant increasing trend in the high altitude area. The HD, CFR, MRV, and MRP were higher in the western region than that in the eastern and national. Those accident indicators tended to increase with increasing altitude. And there were statistically significant differences (p<0.05) among groups from different altitudes. Low-grade roads combined curved and sloping roads, and rollover were significant features associated with traffic accidents in the western region. Over speeding, overloading, bad weather, vehicle failure, and driver error were the top five accident causes. Conclusion: Traffic accidents are increasing in high-altitude areas of western China, and they lead to more severe casualties. The characteristics of serious traffic accidents in this part of the country differ from those of the eastern regions. Improving road safety facilities, restrictions of speed, and improving medical treatment at accident scenes may be effective measures to reduce traffic accidents related injuries in the western region.